What drives the capital structure? The case of non-life insurance companies in Serbia - Božović, Miloš; Koprivica, Marija (Industrija, 2021)
This paper studies the factors behind the capital structure of insurance companies. We use financial reports of non-life and composite insurance companies in Serbia between 2006 and 2019. In particular, we apply a panel-data approach to examine the relationship between leverage, defined as the ratio of technical reserves to capital, and various firm-level characteristics. The coefficients estimated using the individual fixed-effects model indicate a significant and negative influence of profitability, growth and liquidity measures on leverage and a significant and positive influence of company size. These results are in accord with the tradeoff theory and the pecking order theory.
Keywords: non-life insurance; capital structure; leverage; tradeoff theory; pecking order theory